POGLUT1 biallelic mutations cause myopathy with reduced satellite cells, α-dystroglycan hypoglycosylation and a distinctive radiological pattern. - Servián-Morilla, E; Cabrera-Serrano, M; Johnson, K; Pandey, A; Ito, A; Rivas, E; Chamova, T; Muelas, N; Mongini, T; Nafissi, S; Claeys, K G; Grewal, R P; et al. (Acta Neuropathol, 2020)
Protein O-glucosyltransferase 1 (POGLUT1) activity is critical for the Notch signaling pathway, being one of the main enzymes responsible for the glycosylation of the extracellular domain of Notch receptors. A biallelic mutation in the POGLUT1 gene has been reported in one family as the cause of an adult-onset limb-girdle muscular dystrophy (LGMD R21; OMIM# 617232). As the result of a collaborative international effort, we have identified the first cohort of 15 patients with LGMD R21, from nine unrelated families coming from different countries, providing a reliable phenotype-genotype and mechanistic insight. Patients carrying novel mutations in POGLUT1 all displayed a clinical picture of limb-girdle muscle weakness. However, the age at onset was broadened from adult to congenital and infantile onset. Moreover, we now report that the unique muscle imaging pattern of "inside-to-outside" fatty degeneration observed in the original cases is indeed a defining feature of POGLUT1 muscular dystrophy. Experiments on muscle biopsies from patients revealed a remarkable and consistent decrease in the level of the NOTCH1 intracellular domain, reduction of the pool of satellite cells (SC), and evidence of α-dystroglycan hypoglycosylation. In vitro biochemical and cell-based assays suggested a pathogenic role of the novel POGLUT1 mutations, leading to reduced enzymatic activity and/or protein stability. The association between the POGLUT1 variants and the muscular phenotype was established by in vivo experiments analyzing the indirect flight muscle development in transgenic Drosophila, showing that the human POGLUT1 mutations reduced its myogenic activity. In line with the well-known role of the Notch pathway in the homeostasis of SC and muscle regeneration, SC-derived myoblasts from patients' muscle samples showed decreased proliferation and facilitated differentiation. Together, these observations suggest that alterations in SC biology caused by reduced Notch1 signaling result in muscular dystrophy in LGMD R21 patients, likely with additional contribution from α-dystroglycan hypoglycosylation. This study settles the muscular clinical phenotype linked to POGLUT1 mutations and establishes the pathogenic mechanism underlying this muscle disorder. The description of a specific imaging pattern of fatty degeneration and muscle pathology with a decrease of α-dystroglycan glycosylation provides excellent tools which will help diagnose and follow up LGMD R21 patients.
Keywords: Animals; Animals, Genetically Modified; Drosophila melanogaster; Dystroglycans; Female; Genetic Association Studies; Glucosyltransferases; Glycosylation; Humans; Male; Muscle, Skeletal; Muscular Dystrophies, Limb-Girdle; Mutation; Pedigree; Satellite Cells, Skeletal Muscle

Using to drive the diagnosis and understand the mechanisms of rare human diseases. - Link, Nichole; Bellen, Hugo J (Development, 2020)
Next-generation sequencing has greatly accelerated the discovery of rare human genetic diseases. Nearly 45% of patients have variants associated with known diseases but the unsolved cases remain a conundrum. Moreover, causative mutations can be difficult to pinpoint because variants frequently map to genes with no previous disease associations and, often, only one or a few patients with variants in the same gene are identified. Model organisms, such as , can help to identify and characterize these new disease-causing genes. Importantly, allow quick and sophisticated genetic manipulations, permit functional testing of human variants, enable the characterization of pathogenic mechanisms and are amenable to drug tests. In this Spotlight, focusing on microcephaly as a case study, we highlight how studies of human genes in have aided our understanding of human genetic disorders, allowing the identification of new genes in well-established signaling pathways.
Keywords: Animals; Disease Models, Animal; Drosophila melanogaster; Genetic Techniques; Human Genetics; Humans; Microcephaly; Rare Diseases

Ari-1 Regulates Myonuclear Organization Together with Parkin and Is Associated with Aortic Aneurysms. - Tan, Kai Li; Haelterman, Nele A; Kwartler, Callie S; Regalado, Ellen S; Lee, Pei-Tseng; Nagarkar-Jaiswal, Sonal; Guo, Dong-Chuan; Duraine, Lita; Wangler, Michael F; Bamshad, Michael J; Nickerson, Deborah A; Lin, Guang; et al. (Dev Cell, 2018)
Nuclei are actively positioned and anchored to the cytoskeleton via the LINC (Linker of Nucleoskeleton and Cytoskeleton) complex. We identified mutations in the Parkin-like E3 ubiquitin ligase Ariadne-1 (Ari-1) that affect the localization and distribution of LINC complex members in Drosophila. ari-1 mutants exhibit nuclear clustering and morphology defects in larval muscles. We show that Ari-1 mono-ubiquitinates the core LINC complex member Koi. Surprisingly, we discovered functional redundancy between Parkin and Ari-1: increasing Parkin expression rescues ari-1 mutant phenotypes and vice versa. We further show that rare variants in the human homolog of ari-1 (ARIH1) are associated with thoracic aortic aneurysms and dissections, conditions resulting from smooth muscle cell (SMC) dysfunction. Human ARIH1 rescues fly ari-1 mutant phenotypes, whereas human variants found in patients fail to do so. In addition, SMCs obtained from patients display aberrant nuclear morphology. Hence, ARIH1 is critical in anchoring myonuclei to the cytoskeleton.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Animals; Aortic Aneurysm; Carrier Proteins; Cell Nucleus; Child, Preschool; Cytoskeleton; Drosophila melanogaster; Drosophila Proteins; Female; Humans; Male; Middle Aged; Mutation; Myocytes, Smooth Muscle; Pedigree; Phenotype; Ubiquitin-Protein Ligases; Young Adult

Clinically severe CACNA1A alleles affect synaptic function and neurodegeneration differentially. - Luo, Xi; Rosenfeld, Jill A; Yamamoto, Shinya; Harel, Tamar; Zuo, Zhongyuan; Hall, Melissa; Wierenga, Klaas J; Pastore, Matthew T; Bartholomew, Dennis; Delgado, Mauricio R; Rotenberg, Joshua; Lewis, Richard Alan; et al. (PLoS Genet, 2017)
Dominant mutations in CACNA1A, encoding the α-1A subunit of the neuronal P/Q type voltage-dependent Ca2+ channel, can cause diverse neurological phenotypes. Rare cases of markedly severe early onset developmental delay and congenital ataxia can be due to de novo CACNA1A missense alleles, with variants affecting the S4 transmembrane segments of the channel, some of which are reported to be loss-of-function. Exome sequencing in five individuals with severe early onset ataxia identified one novel variant (p.R1673P), in a girl with global developmental delay and progressive cerebellar atrophy, and a recurrent, de novo p.R1664Q variant, in four individuals with global developmental delay, hypotonia, and ophthalmologic abnormalities. Given the severity of these phenotypes we explored their functional impact in Drosophila. We previously generated null and partial loss-of-function alleles of cac, the homolog of CACNA1A in Drosophila. Here, we created transgenic wild type and mutant genomic rescue constructs with the two noted conserved point mutations. The p.R1673P mutant failed to rescue cac lethality, displayed a gain-of-function phenotype in electroretinograms (ERG) recorded from mutant clones, and evolved a neurodegenerative phenotype in aging flies, based on ERGs and transmission electron microscopy. In contrast, the p.R1664Q variant exhibited loss of function and failed to develop a neurodegenerative phenotype. Hence, the novel R1673P allele produces neurodegenerative phenotypes in flies and human, likely due to a toxic gain of function.
Keywords: Alleles; Animals; Animals, Genetically Modified; Calcium Channels; Cerebellar Ataxia; Child; Child, Preschool; Drosophila melanogaster; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Microscopy, Electron, Transmission; Mutation, Missense; Neurodegenerative Diseases; Neuroimaging; Phenotype; Point Mutation

Loss of Nardilysin, a Mitochondrial Co-chaperone for α-Ketoglutarate Dehydrogenase, Promotes mTORC1 Activation and Neurodegeneration. - Yoon, Wan Hee; Sandoval, Hector; Nagarkar-Jaiswal, Sonal; Jaiswal, Manish; Yamamoto, Shinya; Haelterman, Nele A; Putluri, Nagireddy; Putluri, Vasanta; Sreekumar, Arun; Tos, Tulay; Aksoy, Ayse; Donti, Taraka; et al. (Neuron, 2017)
We previously identified mutations in Nardilysin (dNrd1) in a forward genetic screen designed to isolate genes whose loss causes neurodegeneration in Drosophila photoreceptor neurons. Here we show that NRD1 is localized to mitochondria, where it recruits mitochondrial chaperones and assists in the folding of α-ketoglutarate dehydrogenase (OGDH), a rate-limiting enzyme in the Krebs cycle. Loss of Nrd1 or Ogdh leads to an increase in α-ketoglutarate, a substrate for OGDH, which in turn leads to mTORC1 activation and a subsequent reduction in autophagy. Inhibition of mTOR activity by rapamycin or partially restoring autophagy delays neurodegeneration in dNrd1 mutant flies. In summary, this study reveals a novel role for NRD1 as a mitochondrial co-chaperone for OGDH and provides a mechanistic link between mitochondrial metabolic dysfunction, mTORC1 signaling, and impaired autophagy in neurodegeneration.
Keywords: Animals; Autophagy; Drosophila; Drosophila melanogaster; Drosophila Proteins; Ketoglutarate Dehydrogenase Complex; Ketoglutaric Acids; Lysine; Mechanistic Target of Rapamycin Complex 1; Metalloendopeptidases; Mitochondria; Molecular Chaperones; Multiprotein Complexes; Neurodegenerative Diseases; TOR Serine-Threonine Kinases

Mutations in sphingosine-1-phosphate lyase cause nephrosis with ichthyosis and adrenal insufficiency. - Lovric, Svjetlana; Goncalves, Sara; Gee, Heon Yung; Oskouian, Babak; Srinivas, Honnappa; Choi, Won-Il; Shril, Shirlee; Ashraf, Shazia; Tan, Weizhen; Rao, Jia; Airik, Merlin; Schapiro, David; et al. (J Clin Invest, 2017)
Steroid-resistant nephrotic syndrome (SRNS) causes 15% of chronic kidney disease cases. A mutation in 1 of over 40 monogenic genes can be detected in approximately 30% of individuals with SRNS whose symptoms manifest before 25 years of age. However, in many patients, the genetic etiology remains unknown. Here, we have performed whole exome sequencing to identify recessive causes of SRNS. In 7 families with SRNS and facultative ichthyosis, adrenal insufficiency, immunodeficiency, and neurological defects, we identified 9 different recessive mutations in SGPL1, which encodes sphingosine-1-phosphate (S1P) lyase. All mutations resulted in reduced or absent SGPL1 protein and/or enzyme activity. Overexpression of cDNA representing SGPL1 mutations resulted in subcellular mislocalization of SGPL1. Furthermore, expression of WT human SGPL1 rescued growth of SGPL1-deficient dpl1Δ yeast strains, whereas expression of disease-associated variants did not. Immunofluorescence revealed SGPL1 expression in mouse podocytes and mesangial cells. Knockdown of Sgpl1 in rat mesangial cells inhibited cell migration, which was partially rescued by VPC23109, an S1P receptor antagonist. In Drosophila, Sply mutants, which lack SGPL1, displayed a phenotype reminiscent of nephrotic syndrome in nephrocytes. WT Sply, but not the disease-associated variants, rescued this phenotype. Together, these results indicate that SGPL1 mutations cause a syndromic form of SRNS.
Keywords: Aldehyde-Lyases; Animals; Cell Line; Cell Movement; Drosophila melanogaster; Drosophila Proteins; Female; Humans; Ichthyosis, Lamellar; Male; Mesangial Cells; Mice; Mice, Knockout; Mutation; Nephrotic Syndrome; Protein Transport; Rats

Recurrent De Novo and Biallelic Variation of ATAD3A, Encoding a Mitochondrial Membrane Protein, Results in Distinct Neurological Syndromes. - Harel, Tamar; Yoon, Wan Hee; Garone, Caterina; Gu, Shen; Coban-Akdemir, Zeynep; Eldomery, Mohammad K; Posey, Jennifer E; Jhangiani, Shalini N; Rosenfeld, Jill A; Cho, Megan T; Fox, Stephanie; Withers, Marjorie; et al. (Am J Hum Genet, 2016)
ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane protein implicated in mitochondrial dynamics, nucleoid organization, protein translation, cell growth, and cholesterol metabolism. We identified a recurrent de novo ATAD3A c.1582C>T (p.Arg528Trp) variant by whole-exome sequencing (WES) in five unrelated individuals with a core phenotype of global developmental delay, hypotonia, optic atrophy, axonal neuropathy, and hypertrophic cardiomyopathy. We also describe two families with biallelic variants in ATAD3A, including a homozygous variant in two siblings, and biallelic ATAD3A deletions mediated by nonallelic homologous recombination (NAHR) between ATAD3A and gene family members ATAD3B and ATAD3C. Tissue-specific overexpression of bor, the Drosophila mutation homologous to the human c.1582C>T (p.Arg528Trp) variant, resulted in a dramatic decrease in mitochondrial content, aberrant mitochondrial morphology, and increased autophagy. Homozygous null bor larvae showed a significant decrease of mitochondria, while overexpression of bor resulted in larger, elongated mitochondria. Finally, fibroblasts of an affected individual exhibited increased mitophagy. We conclude that the p.Arg528Trp variant functions through a dominant-negative mechanism that results in small mitochondria that trigger mitophagy, resulting in a reduction in mitochondrial content. ATAD3A variation represents an additional link between mitochondrial dynamics and recognizable neurological syndromes, as seen with MFN2, OPA1, DNM1L, and STAT2 mutations.
Keywords: Adenosine Triphosphatases; Adult; Alleles; Animals; ATPases Associated with Diverse Cellular Activities; Axons; Cardiomyopathies; Child; Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Drosophila melanogaster; Female; Fibroblasts; Homozygote; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Muscle Hypotonia; Muscles; Mutation; Nervous System Diseases; Neurons; Optic Atrophy; Phenotype; Polymorphism, Single Nucleotide; Syndrome; Young Adult

A drosophila genetic resource of mutants to study mechanisms underlying human genetic diseases. - Yamamoto, Shinya; Jaiswal, Manish; Charng, Wu-Lin; Gambin, Tomasz; Karaca, Ender; Mirzaa, Ghayda; Wiszniewski, Wojciech; Sandoval, Hector; Haelterman, Nele A; Xiong, Bo; Zhang, Ke; Bayat, Vafa; et al. (Cell, 2014)
Invertebrate model systems are powerful tools for studying human disease owing to their genetic tractability and ease of screening. We conducted a mosaic genetic screen of lethal mutations on the Drosophila X chromosome to identify genes required for the development, function, and maintenance of the nervous system. We identified 165 genes, most of whose function has not been studied in vivo. In parallel, we investigated rare variant alleles in 1,929 human exomes from families with unsolved Mendelian disease. Genes that are essential in flies and have multiple human homologs were found to be likely to be associated with human diseases. Merging the human data sets with the fly genes allowed us to identify disease-associated mutations in six families and to provide insights into microcephaly associated with brain dysgenesis. This bidirectional synergism between fly genetics and human genomics facilitates the functional annotation of evolutionarily conserved genes involved in human health.
Keywords: Animals; Disease; Disease Models, Animal; Drosophila melanogaster; Genetic Testing; Humans; Inheritance Patterns; RNA Interference; X Chromosome